System Modeling and Optimization 23rd IFIP TC 7 Conference, Cracow, Poland, July 23-27, 2007, Revised Selected Papers - Korytowski, Adam; Szymkat, Maciej; Malanowski, Kazimierz; Mitkowski, Wojciech (IFIP Advances in Information and Communication Technology, 2009)
This book is a collection of extended versions of papers presented at the 23rd IFIP TC 7 Conference on System Modeling and Optimization, held in Cracow, Poland, in July 2007. The 29 revised papers were carefully selected from numerous submissions. They cover a wide range of topics including optimzation theory; algorithms of nonlinear optimization; discrete optimization; stochastic optimization; distributed parameter systems: modeling and control; optimal control; stochastic control and financial mathematics; structural design; stability and sensitivity analysis in optimal control; and complex systems.